How has Covid-19 affected the fish feed industry? An analysis on Spectra Hexa Feeds Ltd. - Ahsan, Fariba (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.